DIGITAL GOVERNANCE DALAM PENDIDIKAN: PERAN MEDIASI EFEKTIVITAS GURU PADA PENGARUH TATA KELOLA INFRASTRUKTUR DIGITAL TERHADAP LITERASI KRITIS SISWA - L, Muh Najib; Arismunandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Digital transformation has brought fundamental changes to the way educational institutions are managed, taught, and evaluated for effectiveness. This phenomenon demands an education governance system that can synergistically integrate technology, human, and public policy dimensions. This study aims to analyze the relationship between digital infrastructure governance and students' critical literacy, with teacher effectiveness as a mediating variable. The research approach used is quantitative, employing a Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS). Data were collected online through surveys of 500 teachers and students from various countries that have implemented digital governance policies in education. The results of the study show that digital infrastructure governance has a positive and significant impact on both teacher effectiveness and students' critical literacy, both directly and indirectly. Teacher effectiveness is proven to mediate These effects indicate that successful digital transformation requires strong professional capacity support for teachers. This study provides a theoretical contribution to the development of the concept of digital governance in education as well as practical implications for digital education policy makers at both national and international levels.